Observations of scrotal mass, liver mass, haemolytic jaundice, and central vestibular disorder in brugia pahangi-infected dogs - Vinnie-Siow, Wei Yin; Low, Van Lun; Tan, Tiong Kai; Teoh, Y.B.; Sivanandam, Sinnadurai; Vellayan, Subramaniam; Lim, Yvonne Ai Lian (Malaysian Society of Parasitology and Tropical Medicine, 2019)
Brugia pahangi is known to infect humans and dogs. Its associated symptoms and complications, however, have not been fully understood in dogs. Herein, we reported the observations of B. pahangi infections in dogs with scrotal mass, liver mass, haemolytic jaundice, and central vestibular disorder. © 2019, Malaysian Society for Parasitology. All rights reserved.